ANALISIS SISTEM KERJA SEMPROT HAMA TANAMAN MENGGUNAKAN SOLAR CELL - Anara, Rieza; Alam, Hermansyah; Andinata, Yoffi (Power Elektronik : Jurnal Orang Elektro, 2024)
A sprayer machine that can reduce air pollution and is environmentally friendly by utilizing natural energy, namely sunlight, so that this tool can be used for spraying in plantations by utilizing solar energy sources. In addition to making work easier and faster, the required energy source is also not difficult to obtain, making it more effective and efficient. In the making of such a tool/machine, it is capable of working optimally. In designing the pest sprayer tool, the author uses a 20 wp solar panel which can generate an average daily power (P) of 30.03 watts. A battery with a capacity of 12 volts 7.2 Ah can supply an average power (P) to a 12 volt 3 Ampere DC motor of 9.40 watts when operating. The average power used per hour during the 6-day testing period is 9.40 watts. The time required for the battery to be charged by the solar panel depends on the weather conditions and the intensity of light at the operating location because it affects the high and low current received. The power used to spray pesticide fluid from the tank until it runs out is: 1.6760 Watt.